2020
DOI: 10.3389/fpubh.2020.00429
|View full text |Cite
|
Sign up to set email alerts
|

Social Stigma: The Hidden Threat of COVID-19

Abstract: COVID-19 infection has been recognized as a pandemic by the World Health Organization. Efforts to prevent the spread of the disease are threatened by the appearance of disease-associated social stigma in society. In Egypt, a small wave of stigma directed at different groups started to appear. Here we report the features of COVID-19-associated stigma in Egypt and suggest recommendations to overcome this stigma before it grows and have physical and psychological impacts on society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
127
2
20

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(150 citation statements)
references
References 11 publications
(15 reference statements)
1
127
2
20
Order By: Relevance
“…Studies have shown that during public health emergencies, when immediate and reliable information is required, there are consistently, subgroups of people that are at greater risk of experiencing stigmatisation, discrimination and harassment; hence, will need special attention and protection. 44 45 Efforts to reduce stigmatisation, bullying and harassment associated with COVID-19 cannot be isolated; actions should be the result of proactive collaboration between leaders from diverse sectors of our societies, including but not limited to governments, health organisations, religious leaders and public figures, such as athletes, communicators and social influencers.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that during public health emergencies, when immediate and reliable information is required, there are consistently, subgroups of people that are at greater risk of experiencing stigmatisation, discrimination and harassment; hence, will need special attention and protection. 44 45 Efforts to reduce stigmatisation, bullying and harassment associated with COVID-19 cannot be isolated; actions should be the result of proactive collaboration between leaders from diverse sectors of our societies, including but not limited to governments, health organisations, religious leaders and public figures, such as athletes, communicators and social influencers.…”
Section: Discussionmentioning
confidence: 99%
“…Some features of stigma were reported against medical physicians in Egypt. For example, incidents were reported where taxi drivers did not agree to drive medical physicians, and restaurants would refuse to deliver food to hospitals due to fear of infection with the COVID-19 virus ( 33 ). This explains their feelings of a lack of appreciation of their sacrifices by the society at large during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Social rejection of patients was a concern shared by the participants. Participants agreed that raising awareness about COVID-19 will lead to reduce unjustified social stigma toward patients as indicated in other studies [27,28].…”
Section: Discussionmentioning
confidence: 84%
“…Social stigma has been reported to have impact on people response to disease control and prevention measures [26][27][28][29]. Many participants were not sure if the reason for people getting infected with COVID-19 was due to something they did wrong.…”
Section: Discussionmentioning
confidence: 99%